Escala de avaliação clínica da deglutição na paralisia cerebral - Silverio, Carolina Castelli [UNIFESP] (2016)
Purpose: develop and validate a clinical assessment scale of swallowing in children with cerebral palsy (CP). Methods: the proposed scale was developed based on the assessment scale used by a specialized group in the care of children with CP and dysphagia. After its elaboration the scale had the relevancy and clearness of its items examined for ten expert judges. To verify the reproducibility, the clinical assessment of swallowing was first performed by a expert speech pathologist (Rate A), in 70 children with CP, with varying motor impairment levels, mean age of 4 years and 8 months, through the observation offer of food in paste and liquid consistencies. Swallowing was classified as normal, functional, mild dysphagia, moderate or severe. At the same time, the proposed scale was applied independently by two other expert speech pathologists (Raters B and C). After two weeks, the whole evaluation was performed again. Results: there was a significant difference between swallowing classification and motor impairment level, with worsening dysphagia as there was a worse motor impairment. The scale had consistency and reproducibility efficient. It was possible to make significant cut scores for swallowing classifications set by Rate A, with the exception of normal and functional swallowing classifications that showed the same values. The sensitivity showed great results for the classification normal/functional swallowing, tend to good results for the classifications moderate and severe dysphagia, and poor results for mild dysphagia. Without checking cut scores, it was observed significant difference between mean scores of the classifications of swallowing. Conclusion: the proposed scale showed great rates of consistency and reproducibility, having satisfactory reproducibility; proved to be an efficient tool to differentiate children with CP who presented or not, the dysphagia; tended to establish efficiently the diagnosis of moderate and severe dysphagia, but in a less efficient manner in the establishment of mild dysphagia; proved to be a possible and efficient indicator evolution for the clinical practice of dysphagia in the CP.